2016
DOI: 10.5125/jkaoms.2016.42.5.243
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein/albumin ratio as prognostic score in oral squamous cell carcinoma

Abstract: ObjectivesMany studies have examined histopathological factors and various prognostic scores related to inflammation to predict outcomes. Here, we examined the prognostic value of the C-reactive protein/albumin (CRP/alb) ratio in oral squamous cell carcinoma (OSCC).Materials and MethodsThis retrospective study included 40 patients with OSCC. Using univariate and multivariate analyses, we focused on the correlation of the CRP/alb ratio with clinicopathological characteristics and with overall survival. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…In the same year, Xiao-ling Xu et al and Xiao-li Wei et al had explored the prognostic value of CAR in operable and non-selected ESCC patients, respectively and the area under the curve (AUC) values of the CAR was proved higher than the other inflammation-based prognostic scores at 12 months, 24 months, and 36 months 20 , 21 , which was consistent with our analysis 21 . In addition, similar to the above mentioned reports, the novel but promising CAR has been identified as an independent prognostic factor for OS in our study by multivariate analysis as well 29 , 30 . The summary of these relevant studies are showed in supplementary table (Table S2 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the same year, Xiao-ling Xu et al and Xiao-li Wei et al had explored the prognostic value of CAR in operable and non-selected ESCC patients, respectively and the area under the curve (AUC) values of the CAR was proved higher than the other inflammation-based prognostic scores at 12 months, 24 months, and 36 months 20 , 21 , which was consistent with our analysis 21 . In addition, similar to the above mentioned reports, the novel but promising CAR has been identified as an independent prognostic factor for OS in our study by multivariate analysis as well 29 , 30 . The summary of these relevant studies are showed in supplementary table (Table S2 ).…”
Section: Discussionsupporting
confidence: 91%
“…A total of 10203 patients diagnosed with various cancers, including laryngeal squamous cell carcinoma (LSCC) [ 22 ], ovarian cancer (OC) [ 23 ], renal cell carcinoma (RCC) [ 24 ], non-small cell lung cancer (NSCLC) [ 25 ], pancreatic cancer (PC) [ 26 29 ], colorectal cancer (CRC) [ 30 – 33 ], nasopharyngeal cancer (NPC) [ 21 , 34 36 ], gastric cancer (GC) [ 37 , 42 ], oral squamous cell carcinoma (OSCC) [ 38 ], hepatocellular carcinoma (HCC) [ 39 , 43 ], esophageal squamous cell carcinoma (ESCC) [ 40 , 41 ], small cell lung cancer (SCLC) [ 44 ], were included. These studies originated from China [ 21 24 , 27 , 28 , 33 – 36 , 39 – 42 , 44 ], Japan [ 26 , 30 32 , 37 , 43 ], and Korea [ 25 , 29 , 38 ], respectively. Twenty-three articles reported the outcomes of overall survival (OS) [ 21 31 , 33 – 44 ], and 6 studies presented disease free survival (DFS) as survival endpoint [ 22 , 24 , 26 , 32 , 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three articles reported the outcomes of overall survival (OS) [ 21 31 , 33 – 44 ], and 6 studies presented disease free survival (DFS) as survival endpoint [ 22 , 24 , 26 , 32 , 34 , 37 ]. Seventeen studies included cancer patients with all disease stages (Stage I–IV or limited-extensive stage) [ 22 26 , 28 31 , 34 36 , 38 , 39 , 41 , 43 , 44 ], three studies recruited patients with Stage I–III [ 37 , 40 , 42 ], and four studies reported advanced stages (III, IV, or III-IV) [ 21 , 27 , 32 , 33 ]. The primary treatments were extremely various among these 24 included studies, including surgery [ 22 24 , 26 , 31 , 37 43 ], chemotherapy (CT) [ 21 , 25 , 27 , 29 , 30 , 32 , 33 , 44 ], and concurrent chemoradiotherapy (CCRT) [ 34 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%